A study of clinical profile of patients with chronic obstructive pulmonary disease - Sinha, Teeku; Nalli, Susheel Kumar; Toppo, Amardeepak (International Journal Of Community Medicine And Public Health, 2017)
Background: Chronic morbidity and also deaths are caused by COPD. Once affected by COPD, patients suffer many years together. Some can die before expected life expectancy. It has been estimated that due to constant exposure to risk factor and increased life expectancy, all over the world the prevalence is likely to increase. The objective of the study was to study the clinical profile of patients with chronic obstructive pulmonary disease. Methods: A hospital based cross sectional study was conducted at department of community medicine, Late Baliram Kashyap Memorial Government Medical College, Jagdalpur, Chhattisgarh, India among patients with chronic obstructive pulmonary disease for a period of six months from September 2015 to February 2016. Informed consent was obtained from each patient. Detail clinical history, physical examination to look for nutritional status, spirometry with reversibility was carried out for each and every patient. Results: Age range in our study was 26-75 years. Mean age in COPD patients was 57.13±11.149 years and that of control group was 54.60±13.074 years with male to female ratio 9.71:1 in COPD case and 11.5:1 in control group. Most common symptom in COPD patient was SOB followed by cough, expectoration, and edema and chest pain. mMRC grading in COPD are higher than control group in our study. Smoking in pack year was significantly higher in COPD cases as 69.70± 36.164 and in control group it was 13.84±7.867. Conclusions: COPD was found to be more common in males. Cough was the most common presenting symptom. Smoking was significantly associated with occurrence of COPD.